Genetic variations from successive whole genome sequencing during COVID-19 treatment in five individuals - P. Hemachudha; S. Petcharat; W. Ampoot; T. Ponpinit; L. Paitoonpong; T. Hemachudha (New Microbes and New Infections, 2022)
We report multiple single nucleotide polymorphism taken at different time interval during treatment of COVID-19. Gene sequencing showed mutation within ORF1b at position P314L. Mutation at this point has been shown to impose structural remodelling that increases the affinity for remdesivir binding and may also affect binding affinity for favipiravir.